Cholesterol Levels and Nutritional Composition of Commercial Layers Eggs Fed Diets with Different Vegetable Oils - ABG Faitarone (Revista Brasileira de Ciência Avícola, 2013)
This experiment aimed at evaluating the effects of the supplementation of different vegetable oils at different levels to the diet of commercial layers on egg cholesterol levels and nutritional composition (proteins, total solids, lipids, and ashes) for 112 days. Birds were distributed according to a completely randomized experimental design with 10 treatments (T1 - control; T2 - inclusion of 2.5% rapeseed oil; T3 - inclusion of 2.5% canola oil; T4 - inclusion of 2.5% soybean oil; T5 - inclusion of 5% rapeseed oil; T6 - inclusion of 5% canola oil; T7 - inclusion of 5% soybean oil; T8 - inclusion of 2.5% rapeseed oil + 2.5% soybean oil; T9 - inclusion 2.5% canola oil + 2.5% soybean oil; T10 - inclusion of 2.5% rapeseed oil + 2.5% canola oil) of six replicates of eight birds each, totaling 480 birds. Yolk cholesterol levels and nutritional composition were determined on days 20, 60 and 112 days of the experimental period. Data obtained during the experimental period were submitted to analysis of variance. Egg yolks produced by layer fed oils presented lower cholesterol levels after 20 days of inclusion in the experimental diets. On days 60 and 112, cholesterol levels were higher. It was concluded that supplementing layer diets with vegetable oils rich in polyunsaturated fatty acids does not change the nutritional composition of egg yolks. The supply of diets containing oils rich in polyunsaturated fatty acids does not reduce yolk cholesterol content.